Benzodiazepine use and risk of dementia: evidence from the Caerphilly Prospective Study (CaPS). Issue 10 (27th October 2011) - Gallacher, John; Elwood, Peter; Pickering, Janet; Bayer, Antony; Fish, Mark; Ben-Shlomo, Yoav
Abstract : Background: Benzodiazepine use is widespread in older people, although its benefit is uncertain. Aim: To investigate the long-term effect of benzodiazepine use upon dementia risk. Methods: A prospective cohort of men seen on five occasions over 22 years with full medication histories, repeat measures of cognitive function and a clinical diagnosis of dementia. Results: Of 1134 men with complete data, 103 (9.1%) had been taking benzodiazepines regularly at one or more phases. These men showed a marked increased incidence of dementia (OR=3.50, 95% CI 1.57 to 7.79, p=0.002), which persisted despite adjustment for psychological distress and other covariates. Men exposed in earlier phases showed a greater association than more recent exposure, counter to what one would expect if this was due to reverse causation, though we failed to demonstrate a dose–response effect with drug duration. Conclusion: The taking of benzodiazepines is associated with an increased risk of dementia.